2007
DOI: 10.1007/s00395-007-0680-1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells correlate with endothelial function in patients with coronary artery disease

Abstract: Endothelial progenitor cells (EPC) predict morbidity and mortality in patients at cardiovascular risk.Patients with low EPC counts and impaired endothelial colony forming activity have a higher incidence for cardiovascular events compared to patients with high EPC counts and favorable colony forming activity. The pathophysiological basis for this finding may be an insufficient endothelial cell repair by EPC.We postulate that EPC influence coronary endothelial function which itself is relevant for the outcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 30 publications
4
100
1
4
Order By: Relevance
“…As an important source of renewing injured endothelial cells [2,3] , decreased peripheral EPC numbers and impaired EPC function have been shown to correlate with endothelial dysfunction and atherosclerosis [5] . Many risk factors for coronary artery disease have participated in this pathological process including HHcy [4][5][6] , but the effects of Hcy on EPCs have not been fully clarified until now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important source of renewing injured endothelial cells [2,3] , decreased peripheral EPC numbers and impaired EPC function have been shown to correlate with endothelial dysfunction and atherosclerosis [5] . Many risk factors for coronary artery disease have participated in this pathological process including HHcy [4][5][6] , but the effects of Hcy on EPCs have not been fully clarified until now.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that endothelial progenitor cells (EPCs) may contribute to neovasculogenesis and reendothelialization of damaged blood vessels to maintain the endothelium [2,3] . Some cardiovascular diseases (CVD) and cardiovascular risk factors are associated with lower numbers and dysfunction of circulating EPCs [4][5][6] . Patients or mice with hyperhomocysteinemia (HHcy) have lower numbers of EPCs with impaired activities [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported an inverse correlation between the number of other types of EPC such as the colony‐forming units (or myeloid angiogenic cells) or overall EPC counts (circulating CD34+KDR+ cells), and hypertension, diabetes mellitus, combined Framingham risk factor score, as well as cardiovascular events and death 30, 31, 32. A significant relationship between colony‐forming units and EPC counts (CD133(+) or CD34(+)/KDR(+)) and function, and vascular endothelial function was also reported in patients with cardiovascular diseases 30, 31, 33. The literature presents different EPC subtypes classified according to specific cellular characteristics and function.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow‐derived EPCs play a critical role in vascular re‐endothelialization, angiogenesis and prevention of neointima formation after vascular injury 13, 15, 44. There is an obvious inverse relation between the level of circulating EPCs and the risk of cardiovascular events in the patients with angiographically documented CAD 45. Similarly, impaired function of EPCs such as deficiency in migratory response and poor angiogenic capability has a negative correlation with the severity of CAD 46.…”
Section: Progenitor Cells and Cardiovascular Diseasesmentioning
confidence: 99%
“…The important role of EPCs in maintaining the structural and functional integrity of the blood vessels has been well‐established and extensively discussed in many excellent reviews 47, 48. Thus, the level of circulating EPCs has been an important and independent predictor for cardiovascular outcome in CAD patients 45, and it is crucial to preserve the number and function of EPCs at a healthy level for the normal functionality of vasculature in patients with cardiovascular diseases. A variety of factors are critically involved in the regulation of the in vivo dynamics of EPC number and function, including (but not limited to) cytokines and growth factors like granulocyte‐stimulating colony stimulating factor and VEGF 40, 41, 42, nitric oxide, pharmacological agents like statins 49 and environmental factors like air pollution 19, 50.…”
Section: Progenitor Cells and Cardiovascular Diseasesmentioning
confidence: 99%